Do changes in regulation affect temporary agency workers' job satisfaction? - Busk, Henna; Jahn, Elke J.; Singer, Christine (Berlin, 2015)
"This paper evaluates the impact on temporary agency workers’ job satisfaction of a reform that considerably relaxed regulations covering the temporary help service sector in Germany. We isolate the causal effect of this reform by combining a difference-in-difference and matching approach and using rich survey data. We find that the change of the law substantially decreased agency workers’ job satisfaction while regular workers’ job satisfaction remained unchanged. Further analysis reveals that the negative effect on agency workers’ job satisfaction can be attributed to a decrease in wages and an increase in perceived job insecurity. These results are also robust to the use of different specifications and placebo tests."